2015
DOI: 10.1007/s00011-015-0863-4
|View full text |Cite
|
Sign up to set email alerts
|

NZ suppresses TLR4/NF-κB signalings and NLRP3 inflammasome activation in LPS-induced RAW264.7 macrophages

Abstract: These results indicated that NZ inhibited the generations of NO and pro-inflammatory cytokines by suppressing TLR4/MyD88/NF-κB pathway, suggesting that NZ could be an effective candidate for ameliorating LPS-induced inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…As the receptor of LPS, TLR4 plays a principal role in the recognition of gram‐negative bacteria. MyD88 is an adaptor molecule in response to the interaction of TLR4 with LPS (Xiang et al, ). In the present study, our results showed that LPS treatment increased the protein levels of TLR4, MyD88, and NF‐κB in human MLs.…”
Section: Discussionmentioning
confidence: 99%
“…As the receptor of LPS, TLR4 plays a principal role in the recognition of gram‐negative bacteria. MyD88 is an adaptor molecule in response to the interaction of TLR4 with LPS (Xiang et al, ). In the present study, our results showed that LPS treatment increased the protein levels of TLR4, MyD88, and NF‐κB in human MLs.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that NLRP3 promoter contains a putative NFκB binding site and NFκB inhibition resulted in a significant reduction of NLRP3 expression54. Meanwhile, mounting evidence suggests that NLRP3 inflammasome formation is positively associated with NFκB activity5556. All these findings implied that the pro-tumorigenic ability of NFκB might be attributed to inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also demonstrated that NLRP3 promoter contains putative NF-κB binding site and NF-κB inhibition resulted in a significant reduction of NLRP3 expression [39]. Meanwhile, mounting evidence suggested that NLRP3 inflammasome formation is positively associated with NF-κB activity following drug treatment such as LPS, CPT-11, FGF-21, etc [40-42]. All these findings implied that the pro-tumorigenic ability of NF-κB might be attributed to inflammasome activation.…”
Section: Regulation Of Inflammasome Activationmentioning
confidence: 99%